1983
DOI: 10.1042/bj2140011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and growth factors stimulate the phosphorylation of a Mr-22000 protein in 3T3-L1 adipocytes

Abstract: Insulin, epidermal growth factor (EGF), platelet-derived growth factor, multiplication-stimulating activity and 10% foetal-calf serum each stimulated the phosphorylation of a cytosolic Mr-22000 acidic heat-stable protein in Swiss mouse 3T3-L1 adipocytes. Phosphorylation of this protein was not stimulated by isoprenaline or dibutyryl cyclic AMP. The effect of insulin was maximal (3-fold increase) by 10 min; half-maximal stimulation was observed at 70 pM-insulin. Both [32P]phosphoserine and [32P]phosphothreonine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 23 publications
3
40
0
Order By: Relevance
“…The inability of alkaline phosphatase to convert the ~-form may be due to inaccessibility of the phosphate residue or a difference in amino acid residues that are dephosphorylated. It has been shown that PHAS-I can be phosphorylated at serine as well as threonine residues [10]. Second, azp labeling of cells showed two phoshorylated PHAS-I forms [4,9,30], and their migration on SDS-PAGE indicates that these phosphorylated forms are the [3-and y-form.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The inability of alkaline phosphatase to convert the ~-form may be due to inaccessibility of the phosphate residue or a difference in amino acid residues that are dephosphorylated. It has been shown that PHAS-I can be phosphorylated at serine as well as threonine residues [10]. Second, azp labeling of cells showed two phoshorylated PHAS-I forms [4,9,30], and their migration on SDS-PAGE indicates that these phosphorylated forms are the [3-and y-form.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that PHAS-I is mostly phosphorylated at serine residues in control cells, but at threonine residues in insulin-treated cells [10]. This suggests that more than one kinase is involved in PHAS-I phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of the mechanism, to the extent that eIF-4E is involved in the control of mitogenesis, PHAS-I is also implicated as it is a regulator of eIF-4E. The phosphorylation of PHAS-I and release of eIF-4E are stimulated by several mitogens, including insulinlike growth factor-1, platelet-derived growth factor BB, and epidermal growth factor [11,41]. As suggested previously [11,12], the dephosphorylation of PHAS-I produced by rapamycin could be involved in the antiproliferative effects of the agent.…”
Section: Discussionmentioning
confidence: 99%